Complaints Regarding Trademark Crimes Against Trademark Holders and Consumer Protection - Devica Rully Masrur; Irawati Irawati; Antonius Alexander Tigor (Jurnal Pembangunan Hukum Indonesia, 2025)
The background of this paper is the existence of illegal trademark infringement according to the Trademark and Geographical Indications Law on registered trademarks by other parties, especially for the same or similar goods or services that have the potential to mislead consumers. Referring to this, trademark crimes can only be reported as absolute offenses that can only be reported by trademark holders. The purpose of this study is to examine the mechanism of absolute offenses in the enforcement of trademark criminal law in Indonesia based on the Trademark and Geographical Indications Law, as well as its implications for the protection of trademark holders and consumers. This research is normative legal research with a legislative approach. The results of the study state that the initiation of criminal proceedings is entirely through the mechanism of absolute complaint offenses. However, these absolute complaint offenses have the potential to hinder the enforcement of trademark infringement laws, because the provisions of complaint offenses in trademark crimes are also not in line with the objectives of consumer protection as stipulated in the Consumer Protection Law. The conclusion obtained from this study is based on the theory of Roscoe Pound's balance and Pancasila Prismatics, it is necessary to re-arrange the absolute complaint offense from trademark crimes to relative complaint offenses. Thus, consumers as parties who are directly harmed by the circulation of counterfeit goods have the legitimacy to file a criminal trademark complaint